Recoupling Economic and Social Prosperity - Katharina Lima de Miranda; Dennis J. Snower (Institute of Labor Economics (IZA), 2020)
This paper explores a new theoretical and empirical approach to the assessment of human well-being, relevant to current challenges of social fragmentation in the presence of globalization and technological advance. We present two indexes of well-being – solidarity (S) and agency (A) – to be considered alongside the standard indexes of material gain (G) and environmental sustainability (E). The four indexes – SAGE – form a balanced dashboard for evaluating well-being. The solidarity index covers the needs of humans as social creatures, living in societies that generate a sense of social belonging. The agency index involves people's need to influence their fate through their own efforts. While "economic prosperity" (material gain) is conventionally measured through GDP per capita, "social prosperity" can be measured through our solidarity and agency indexes, alongside environmental sustainability that is measured through the Environmental Performance Index. The SAGE dashboard is meant to provide a "sage" approach to assessing well-being, since it aims to denote sagacity in the pursuit and satisfaction of fundamental human needs and purposes. Many of the prominent challenges of the twenty-first century, including the dissatisfaction of population groups who feel left behind by globalization and technological advance, may be viewed in terms of a "decoupling" of economic prosperity from social prosperity. We present a theoretical model that provides a new perspective on the welfare effects of globalization and automation. The dashboard is meant to provide an empirical basis for mobilizing action in government, business and civil society to promote a recoupling of economic and social prosperity.
Keywords: I31; O11; D63; D91; A13; B55; F01; F60; H11; 330; Beyond GDP; inequality; empowerment; social cohesion; social inclusion; social solidarity; social sustainability; well-being